Discipleship in the context of judaism in Jesus’ time : part 1 - Gracin, Martina, teologinja (Array, 2019)
The usage of the terms “disciple” and “discipleship” are very common among evangelical Christians and meanings of these terms seem self-evident. However, although these circles adopted such language, it was already present in the Jewish culture of Jesus’ time. The purpose and the goal of this article is to analyze the concept of discipleship in its original context and see how much the meaning of this term is removed from the meaning that this term has today. This topic we will address in two parts. In the first chapter, we will study the Old Testament (OT) roots of discipleship, and in the second chapter, the Jewish educational system in Jesus’ time. In the third chapter, we will analyze whether Jesus himself, and in what measure, passed through that Jewish educational system, and how and in what ways he used this model in the discipleship process of his disciples. In the second part of the article, we will address the practice of discipleship in the first Church, and after that offer some guidelines on how to apply Jesus’ concept of discipleship in the Church today. The key focus of this article is the problematic of applying principles of discipleship that were present in the context of Jewish culture, on the Church today, since our analysis reveals that understanding of discipleship today does not correspond entirely to the understanding of that concept in Jesus’ time. Although discipleship then and now contained passing on information, more importantly was to follow the rabbi and learn from him in a close relationship. It is concluded that a possible solution for this challenge must be sought first and foremost in the change of thinking about what discipleship truly is (change of focus), and then in the practice through mentoring or working in small groups purposefully expose both sides (both “teachers” and “students”) to the experience of teaching through example.